Concurrent and lagged relationships among various drought indices in the United states - SOULE, PETER T. (MAUSAM, 1992)
The purpose of this study is to examine the nature of the concurrent and lagged relationships among various drought type-specific measures of drought severity. Monthly values of average temperature (TEMPZ), total precipitation (PREZ), the Palmer moisture anomaly index (ZINX) the Palmer drought severity index (PDSl), and the Palmer hydrologic drought seventy Index (PHDI) were examined from a sample of climatic divisions, in the United States for the period,1931-1985. The relationships are examined at two levels through the use of simple correlations. Level one utilizes data from the entire study period. Data from selected drought events are employed in level two. The results show that the strongest relationships are between drought indices with similar rates of response to changes in moisture supply and demand. The correlations also show that lagged values of fast-response drought indices (ZINX, PREZ) arc more strongly correlated with the slow-response PHD1 than concurrent values. Intersite differences between correlated pairs of indices are generally small and follow consistent trends; cross the flow pattern sample for both level one and level two analyses. Intra-site differences are large for some pairs of correlated indices indicating that characteristics of individual droughts can deviate substantially from average or normal conditions